2015
DOI: 10.1007/s11244-015-0437-2
|View full text |Cite
|
Sign up to set email alerts
|

Deep Hydrodesulfurization of Dibenzothiophenes Over NiW Sulfide Catalysts Supported on Sol–Gel Titania–Alumina

Abstract: This work showed that the use of Al 2 O 3 -TiO 2 as carriers has a positive effect on the activity of supported NiW catalysts in the hydrodesulfurization of dibenzothiophene and 4,6-dimethyldibenzothiophene carried out in a batch reactor at 320°C and total H 2 pressure of 5.5 MPa. Two Al 2 O 3 -TiO 2 mixed oxides with Al/Ti atomic ratios of 10 and 2 were synthesized by sol-gel method together with the pure Al 2 O 3 synthesized as reference support. For NiW/ Al 2 O 3 -TiO 2 and NiW/Al 2 O 3 catalysts, a metal l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
1
20
0
1
Order By: Relevance
“…The obtained gel was aged for 24 h at 273 K. Subsequently, it was dried at 333 K. Finally, the dried gel was calcined for 3 h at 773 K with a rate of 3 K min −1 . AT2 support textural properties were: S BET = 359 m 2 g −1 , V p = 1.1 cm 3 g −1 , Dp = 7.7 nm, and PZC = 7.6, as previously reported by [32,34] The promoted CoMo catalyst series were impregnated following four different molar Co/(Co + Mo) ratios: 0.1, 0.2, 0.3, and 0.4. For monometallic catalysts, the Mo (or Co) solution was impregnated on AT2 support and was macerated at room conditions for 12 h. After that, it was dried at 393 K and calcinated at 673 K for 5 h. For the promoted catalyst, the Mo calcined materials were impregnated with the cobalt solution and the heat treatment was repeated.…”
Section: Support Synthesissupporting
confidence: 55%
See 3 more Smart Citations
“…The obtained gel was aged for 24 h at 273 K. Subsequently, it was dried at 333 K. Finally, the dried gel was calcined for 3 h at 773 K with a rate of 3 K min −1 . AT2 support textural properties were: S BET = 359 m 2 g −1 , V p = 1.1 cm 3 g −1 , Dp = 7.7 nm, and PZC = 7.6, as previously reported by [32,34] The promoted CoMo catalyst series were impregnated following four different molar Co/(Co + Mo) ratios: 0.1, 0.2, 0.3, and 0.4. For monometallic catalysts, the Mo (or Co) solution was impregnated on AT2 support and was macerated at room conditions for 12 h. After that, it was dried at 393 K and calcinated at 673 K for 5 h. For the promoted catalyst, the Mo calcined materials were impregnated with the cobalt solution and the heat treatment was repeated.…”
Section: Support Synthesissupporting
confidence: 55%
“…One possible way is to modify Al-based mixed oxides, such as Al 2 O 3 -TiO 2 (AT). This mixed oxide has been proposed as an alternative support to take advantage of the combined properties of alumina and titania [27][28][29][30][31][32][33]. It had displayed notorious improvements in the textural and physicochemical properties in comparison to alumina or titania supports [30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies showed for example that Mo over Al/Ti = 1 and Ti/(Ti + Zr) = 0.8 supports lead to the highest activities among tested catalysts for hydrocracking and coal-derived liquids upgrading [69]. For the HDS of DBT, several reports have been published using Al/Ti = 2 to obtain the highest activity [4,35,52,55] among materials prepared by the sol-gel method.…”
Section: Mixed Oxides Support: a Different Approachmentioning
confidence: 99%